THE IMPACT OF PLANTING SPACING ON THE GROWTH AND YIELD OF GREEN BUTTERHEAD LETTUCE (Lectuca sativa var. capitata L.) IN SWU 02 SMART WATERING HYDROPONIC SYSTEM. - Dwi Rahayu Purbasari; Nurpilihan Bafdal; Sophia Dwiratna Nur Perwitasari (J-PEN Borneo : Jurnal Ilmu Pertanian, 2023)
The growth of the human population has resulted in the conversion of agricultural land into residential areas, and one potential solution to this issue is utilizing hydroponic technology for agriculture. The Smart Watering SWU02 hydroponic system is one type of hydroponic technology that can be employed for this purpose. Proper spacing plays a crucial role in hydroponics because it can impact plant growth and development. Therefore, the objective of this study was to examine the impact of spacing on the growth and yield of green butterhead lettuce (Lectuca sativa var. capitata L.). A completely randomized design (CRD) with three treatments, consisting of 12.5 x 12.5 cm, 20x20cm, and 25 x 25 cm spacing, each replicated three times, was used in this study. The results demonstrated that plant spacing significantly affected plant growth and yield. Planting lettuce with a spacing of 25 x 25 cm resulted in the best outcomes and had a significant impact on plant growth and yield compared to other spacing options, with a plant height growth of 18.33 cm, a plant width of 31.17 cm, a yield of plant weight of 122.78 grams, and a distance between leaves of 0.03 cm. Optimal plant growth and avoiding etiolation symptoms can be achieved by spacing plants apart, which minimizes competition for nutrients.Keywords: Green Butterhead Lettuce., Hydroponics, Planting Spacing, Plant Yield